Cretaceous–Paleogene plant extinction and recovery in Patagonia. Issue 4 (November 2020) - Stiles, Elena; Wilf, Peter; Iglesias, Ari; Gandolfo, María A.; Cúneo, N. Rubén
Abstract: The Cretaceous–Paleogene (K/Pg) extinction appears to have been geographically heterogeneous for some organismal groups. Southern Hemisphere K/Pg palynological records have shown lower extinction and faster recovery than in the Northern Hemisphere, but no comparable, well-constrained Southern Hemisphere macrofloras spanning this interval had been available. Here, macrofloral turnover patterns are addressed for the first time in the Southern Hemisphere, using more than 3500 dicot leaves from the latest Cretaceous (Maastrichtian) and the earliest Paleocene (Danian) of Argentine Patagonia. A maximum ca. 90% macrofloral extinction and ca. 45% drop in rarefied species richness is estimated across the K/Pg, consistent with substantial species-level extinction and previously observed extirpation of host-specialized leaf mines. However, prior palynological and taxonomic studies indicate low turnover of higher taxa and persistence of general floral composition in the same sections. High species extinction, decreased species richness, and homogeneous Danian macrofloras across time and facies resemble patterns often observed in North America, but there are several notable differences. When compared with boundary-spanning macrofloras at similar absolute paleolatitudes (ca. 50°S or 50°N) from the Williston Basin (WB) in the Dakotas, both Maastrichtian and Danian Patagonian species richnesses are higher, extending a history of elevated South American diversity into the Maastrichtian. Despite high species turnover, our analyses also reveal continuity and expansion of leaf morphospace, including an increase in lobed and toothed species unlike the Danian WB. Thus, both Patagonian and WB K/Pg macrofloras support a significant extinction event, but they may also reflect geographically heterogeneous diversity, extinction, and recovery patterns warranting future study.